Biomedical applications of collagens. Issue 4 (7th October 2015) - Ramshaw, John A. M.
Abstract: Collagen‐based biomedical materials have developed into important, clinically effective materials used in a range of devices that have gained wide acceptance. These devices come with collagen in various formats, including those based on stabilized natural tissues, those that are based on extracted and purified collagens, and designed composite, biosynthetic materials. Further knowledge on the structure and function of collagens has led to on‐going developments and improvements. Among these developments has been the production of recombinant collagen materials that are well defined and are disease free. Most recently, a group of bacterial, non‐animal collagens has emerged that may provide an excellent, novel source of collagen for use in biomaterials and other applications. These newer collagens are discussed in detail. They can be modified to direct their function, and they can be fabricated into various formats, including films and sponges, while solutions can also be adapted for use in surface coating technologies. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 665–675, 2016.